Persistence: the key to legume performance in summer-dry hill country - Dodd, M.B.; Sheath, G.W. (NZGA: Research and Practice Series, 2003)
In North Island hill country, a number of environmental and management factors interact to limit the performance of herbaceous legumes in pasture swards. Summer-autumn moisture stress appears to be the dominant influence, particularly because of its irregularity. Legume performance is a function of establishment success, persistence and productivity. Long-term persistence of genotypes in particular should be a primary focus in the development of new germplasm. Secondary to this is the importance of improving herbage productivity and quality. We present evidence for this view from field studies of white and subterranean clover, as well as preliminary examinations of other legume species. Key characteristics contributing to enhanced persistence are prostrate growth forms with high numbers of growing points below the grazing horizon; nodal rooting and root tolerance of low soil pH; flowering patterns that are timed to avoid the dry period, yet sufficiently flexible to cope with the unpredictability of that period; and seed mechanisms that protect against "false strike" following shortlived summer rains. Key words: clover, hill country, legumes, persistence, summer-dry